Procedural fairness in ethnic-cultural decision-making: fostering social cohesion by incorporating minority and majority perspectives - Dierckx, Kim; Van Hiel, Alain; Valcke, Barbara; van den Bos, Kees (Frontiers in Psychology, 2023)
Recent research describes how procedural fairness can be used to resolve issues related to ethnic-cultural matters. The central finding in this strand of literature is that when minority members experience procedurally fair treatment by societal actors regarding ethnic-cultural issues, this will lead to a range of outcomes that are beneficial for social cohesion. Although these results are promising, it remains yet to be shown that such group-specific treatment fairness does not hamper social cohesion by inciting misapprehension among members of non-recipient groups. Therefore, the present study set out to examine two central questions. First, how would minority group members respond to treatment fairness of citizens belonging to another minority group? Second, how would majority group members respond to treatment fairness of citizens belonging to minority groups? Two experimental studies (total N = 908) examined these questions. In Study 1, we compared ethnic-cultural minorities’ reactions to procedurally (un)fair treatment of their own versus a different minority group. In Study 2, we compared minority and majority group members’ responses to procedurally (un)fair treatment of minority group members. Results show that minority group member reactions to ethnic-cultural procedural fairness emanate from a shared bond with the fairness recipient(s) of the other minority group. Conversely, majority group members’ reactions are driven primarily by a perceived moral obligation to act rightfully towards members of disadvantaged groups. Taken together, our results suggest that ethnic-cultural procedural fairness enactment fosters societal unity among different groups, possibly strengthening social cohesion for well-being and prosperity among members of these groups.